The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/en14186004
|View full text |Cite
|
Sign up to set email alerts
|

A Critical Review of Experimental Investigations about Convective Heat Transfer Characteristics of Nanofluids under Turbulent and Laminar Regimes with a Focus on the Experimental Setup

Abstract: In this study, several experimental investigations on the effects of nanofluids on the convective heat transfer coefficient in laminar and turbulent conditions were analyzed. The aim of this work is to provide an overview of the thermal performance achieved with the use of nanofluids in various experimental systems. This review covers both forced and natural convection phenomena, with a focus on the different experimental setups used to carry out the experimental campaigns. When possible, a comparison was perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 71 publications
0
6
0
Order By: Relevance
“…This topic is growing in importance, and many works have been published so far exploring different aspects. In particular, the work by Colangelo et al [1] is a review of the experimental convective thermal performance of various nanofluids obtained in different working conditions (turbulent and laminar) with an in-depth focus on the experimental setups used for the scientific campaigns. The authors highlighted that in the examined works, the nanofluids always showed a significant improvement in the convective heat transfer coefficient, but with big data dispersion.…”
Section: Overviewmentioning
confidence: 99%
“…This topic is growing in importance, and many works have been published so far exploring different aspects. In particular, the work by Colangelo et al [1] is a review of the experimental convective thermal performance of various nanofluids obtained in different working conditions (turbulent and laminar) with an in-depth focus on the experimental setups used for the scientific campaigns. The authors highlighted that in the examined works, the nanofluids always showed a significant improvement in the convective heat transfer coefficient, but with big data dispersion.…”
Section: Overviewmentioning
confidence: 99%
“…The motivation for nanofluids can be traced back to Maxwell’s prediction of improving the thermal conductivity of liquids using solid particles [ 3 ]. Nanofluids have been found to possess enhanced thermo-physical properties such as thermal conductivity, thermal diffusivity, viscosity, and convective heat-transfer coefficients compared to traditional heat-transfer fluids [ 4 ]. Nanofluids might be generated in a single base fluid or a single-phase liquid mixture.…”
Section: Introductionmentioning
confidence: 99%
“…They found that a high Peclet number and bio-convection Lewis number lessen the microorganism profiles, but enhance them for high melting parameter values. By considering the impact of Cattaeneo–Christov and convective conditions, Rasool and Wakif [ 27 ] analyzed second-grade flow of nanofluids over a Riga plate and used the spectral local linearization method to find the solution to the problem. Colangelo et al [ 28 ] performed experimental measurements and showed that nanofluids enhance the rate of heat transfer.…”
Section: Introductionmentioning
confidence: 99%